Genotyping by Sequencing of Cultivated Lentil (Lens culinaris Medik.) Highlights Population Structure in the Mediterranean Gene Pool Associated With Geographic Patterns and Phenotypic Variables - Pavan, Stefano; Bardaro, Nicoletta; Fanelli, Valentina; Marcotrigiano, Angelo Raffaele; Mangini, Giacomo; Taranto, Francesca; Catalano, Domenico; Montemurro, Cinzia; De Giovanni, Claudio; Lotti, Concetta; Ricciardi, Luigi (Frontiers in Genetics, 2019)
Cultivated lentil (Lens culinaris Medik.) is one of the oldest domesticated crops and one of the most important grain legumes worldwide. The Mediterranean Basin holds large part of lentil biodiversity, however no genetic structure was defined within the Mediterranean gene pool. In this study, we used high-throughput genotyping by sequencing (GBS) to resolve the genetic structure of the Mediterranean ex situ lentil collection held at the Italian National Research Council. Sequencing of a 188-plex GBS library and bioinformatics treatment of data yielded 6,693 single nucleotide polymorphisms (SNPs). Analysis of non-redundant genotypes with non-parametric and parametric methods highlighted the occurrence of five highly differentiated genetic clusters. Clustering could be related to geographic patterns and phenotypic traits, indicating that post-domestication routes introducing cultivation in Mediterranean countries and selection were major forces shaping lentil population structure. The estimation of the fixation index FST at individual SNP loci allowed the identification of distinctive alleles across clusters, suggesting the possibility to set-up molecular keys for the assignment of lentil germplasm to specific genetic groups. Finally, significant associations between markers and phenotypic data were identified. Overall, the results of this study are of major importance for lentil conservation genetics and breeding and provide insights on the lentil evolutionary history.